Coaches' perceptions of athletes' stress-related growth following sport injury - Wadey, R.; Clark, S.; Podlog, L.; McCullough, D. (Psychology of Sport and Exercise, 2013)
Objective: The objective of this study was to examine coaches' perceptions of athletes' stress-related growth following sport injury. Design: Qualitative inquiry, grounded in a post-positivism paradigm was used to gain an in-depth understanding of the study's objective. Method: A purposeful sample of eight coaches (M age=45.7; SD=11.2) were interviewed across different sports and competitive standards. The semi-structured life world interviews were analysed using content analysis, and two trustworthiness procedures were employed to bolster the rigour of the findings (i.e., peer-debriefing and member checking). Results: Findings revealed four general dimensions of stress-related growth: personal growth (e.g.,beliefs), psychological growth (e.g., sporting qualities), social growth (e.g., social support), and physical growth (e.g., strength). The coaches also reported a number of behavioural indicators that reflected the four general dimensions (e.g., health and performance). Conclusions: Findings `validate` or provide coherence with athletes' self-reports of stress-related growth in previous research and also extend the literature by identifying a number of novel types of growth and perceived behavioural correlates. Future avenues of research include the need to conduct prospective studies and explore related concepts (e.g., vicarious stress-related growth).